Madecassoside Protects Against LPS-Induced Acute Lung Injury via Inhibiting TLR4/NF-κB Activation and Blood-Air Barrier Permeability - Peng, Lu-Yuan; Shi, Hai-Tao; Yuan, Meng; Li, Jing-He; Song, Ke; Huang, Jiang-Ni; Yi, Peng-Fei; Shen, Hai-Qing; Fu, Ben-Dong (Frontiers in Pharmacology, 2020)
Madecassoside (MA), a crucial ingredient of Centella asiatica, has been reported to exhibit a variety of bioactivities, including anti-pulmonary fibrosis, and anti-inflammatory effects. Here we aimed to elucidate the protective activity and underlying mechanisms of MA with a focus on acute lung injury (ALI). The mice were received intratracheal of LPS to establish the ALI model and treated with MA. Then we measured the pathological changes by haematoxylin and eosin staining, the levels of pro-inflammatory cytokines and myeloperoxidase (MPO) by ELISA, the transcriptional level of tight junction proteins by qRT-PCR, as well as the expression of Toll-likereceptor4/Nuclear factor kappa-B (TLR4/NF-κB) pathway by western blot. The results indicated that MA significantly inhibited LPS-induced pathological damages, lung edema, MPO activity, and pro-inflammatory cytokines production. Furthermore, MA obviously reduced alveolar epithelium permeability which showed by reduced secretion of total proteins in the BALF and enhanced mRNA expression of tight junction as Occludin and zonula occludens-1 (ZO-1) comparing to LPS. Further research indicated that the LPS stimulation up-regulated the TLR4/NF-κB signaling pathway and the up-regulation were reversed by MA. In conclusion, these data supported that MA had protective effects on LPS-induced ALI. The therapeutic possibility may be associated with reducing the alveolar epithelium permeability and inflammatory response via repressing the activation of TLR4/NF-κB pathway.